Tiny hands in unorganised sector : towards elimination of child labour - Mishra, S. N., 1942-; Mishra, Sweta, 1971- (New Delhi : Shipra Publications, 2004)
In the Indian context; with particular reference to Delhi, India.
Includes bibliographical references (p. [168]-184) and index.
Keywords: Child labor -- India -- Delhi; Child labor -- Law and legislation -- India -- Delhi